Primary fistulectomy of congenital lacrimal fistula: A case report - Muhammed Mustafa Kurt; Cetin Akpolat; Ferhat Evliyaoglu (Medicine Science, 2018)
A 13-month-old male patient presenting with epiphora and discharge in his left eye present since birth was assessed in our clinic. Epiphora and an orifice of fistulae next to the left nasal root were identified via physical examination. Punctual mucoid discharge was observed following a massage of the left lacrimal sac. Chronic lacrimal fistulae were diagnosed in terms of stain outflow from the fistula orifice following a trypan blue injection to the lacrimal sac under general anesthesia. The patency of the distal nasolacrimal duct was confirmed by performing lavage following the fistulectomy procedure. The epiphora disappeared and the nasolacrimal passage was open in post-operative care. [Med-Science 2018; 7(4.000): 949-50]